Coaching leadership as a link between individual- and team-level strength use at work - Liisa Mäkelä; Hilpi Kangas; Eveliina Korkiakangas; Jaana Laitinen (Cogent Business & Management, 2024)
This qualitative study delves into the interplay between coaching leadership and the utilization of strengths at both individual and team levels. Despite the acknowledged significance of this interplay, there is a scarcity of empirical qualitative research in this domain. Thus, this study aimed to address this gap by examining the prevalence and effectiveness of coaching leadership practices and strength use. Through a qualitative research approach, data from 17 supervisors and 23 employees within elderly care units were analyzed using template analysis. The outcomes of this study underscore the pivotal role of leadership in facilitating the application of strengths within the workplace, highlighting the interconnectedness of individual and team-level strength utilization. The findings of this study reveal that leadership plays a pivotal role in enabling and facilitating strength use at work, and that individual- and team-level strength use are linked. Leaders need to personally know their team members at the individual level, empower teams to work autonomously, and create a safe, open atmosphere for diversity at the team level. Adopting qualitative methodology, the study comprehends how coaching leadership facilitates strength utilization. This nuanced approach contributes to literature, enhancing our understanding of leadership's role in optimizing strengths in a professional context.
Keywords: 650; leadership; coaching leadership; elderly care; health care; strength use